Pengembangan dan Pengelolaan Adat Budaya Melalui Pembentukan Rancangan Peraturan Desa Dongko, Kabupaten Trenggalek - Muhammad Marcellino Putra Putra Syadila; Nela Erdianti; Ravenzka Ash Shafa Chikita Jasmine; Yana Indawati (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
The Trenggalek Regency is home to Dongko Village, which is found in the Dongko District. Dongko Village is one of the potential Tourism Villages because of the rich variety of its traditions and histories. Dongko's cultural customs are an integral part of the village's identity and must be safeguarded in both their physical and legal manifestations if the village is to continue to grow and be managed effectively. Empirical study was conducted, which depicts an investigative process present in all areas of social life, including volunteer work. The term